Rehydration methods to recover cysticercoids of the rat tapeworm Hymenolepis diminuta from dry flour beetle carcasses. Issue 4 (10th June 2016) - Chin, H.M.-H.; Luong, L.T.; Shostak, A.W.
Abstract: Terrestrial arthropods host a variety of helminth parasites, yet quantifying the intensity of infection in these hosts post-mortem is challenging because carcasses may desiccate quickly. We recovered cysticercoids of Hymenolepis diminuta from desiccated flour beetle ( Tribolium confusum ) carcasses by modifying a published insect rehydration procedure. Without rehydration, carcasses dissected more than 1 day post-mortem had noticeable degradation of cysticercoids. Mild rehydration (soaking in water only for 2 days, or 0.5–10% KOH for 1 h followed by 1 day in water, or 0.5% KOH for 1 day) left carcasses tough and time-consuming to dissect, but all parasites could be recovered and were similar in body size to fresh cysticercoids. Moderate rehydration (5–10% KOH for 1 day) allowed all parasites to be recovered and facilitated dissection by partially dissolving internal organs of the beetle while causing little degradation of the cysticercoids. Harsh rehydration (5–10% KOH for 1 day followed by 5 days in water) not only dissolved internal beetle tissues but also severely damaged cysticercoids, such that parasite counts were unreliable. The degree of initial carcass desiccation had little effect on results following rehydration. However, regardless of treatment used, intact cercomers were rarely retained on rehydrated cysticercoids. Rehydration was less successful on early developmental stages of the parasite, which were recovered reliably only as they neared the cysticercoid stage. This method has utility for studies of parasite-induced mortality by permitting accurate and reliable parasite counts from dead, desiccated hosts.